DEVELOPING INTENSIVE READING MATERIALS INTEGRATED WITH ISLAMIC VALUES FOR SHARIA FACULTY STUDENTS - Yuni Amelia; Prisna Aswarita Putri (International Journal of English Learning and Applied Linguistics (IJELAL), 2026)
The absence of contextually relevant English intensive reading materials for Islamic law students in Indonesian Islamic universities represents a significant pedagogical gap. This study aimed to develop ESP intensive reading materials integrated with Islamic values for first-year students at the Faculty of Sharia, UIN Datokarama Palu. Employing a Research and Development (R&D) design based on the 4D model (Define, Design, Develop), this study involved first-year students from four departments: Family Law, Islamic Economic Law, Comparative Madhab, and Islamic Constitutional Law, whose English proficiency was identified at CEFR A1–A2 level. A needs analysis was conducted through observation, document review, and lecturer interviews, revealing the absence of discipline-specific reading materials within the faculty. Based on these findings, six reading units were developed covering core Islamic law topics: Fiqh Ibadah, Muamalah, Zakat, Munakahat, Mawarish, and Wakaf. The developed materials were validated by three experts, two Islamic Law experts and one ESP/language expert, with an overall validation score of 94.55%, categorized as Very Valid. The findings confirm that needs-based, context-specific ESP materials integrating Islamic values are both feasible and pedagogically appropriate for Sharia Faculty EFL learners.